(untitled) (Global Journal of Management and Business Research, 2020)
The paper argued that the challenges experienced in Nigerian textile manufacturing firms resulted from weak strategic entrepreneurship leading to alarming decline in the industry’s performance. Thus, investigated competitive advantage nexus with strategic entrepreneurship (strategic flexibility, adaptability, innovation, strategic leadership, risk taking and dynamic capabilities) as proxies in Lagos State, Nigeria. A cross-sectional survey research design was used and primary data collected. The adapted questionnaire validity was established through confirmatory factor analysis while the reliability was ascertained through internal consistency test. The population consists of 253 senior management staff and total enumeration was used. A total of 253 copies of the questionnaire were administered but 237 copies reverted. Descriptive statistics, exploratory analysis and structural equation model were utilized to analyse the data.